Prostor v folklorni književnosti - Babšek, Andreja (Revija za elementarno izobraževanje, 2011)
The Concept of Space in Folk Literature. Space is a philosophical and real category that is inseparably connected with time; together they form a comprehensive unit. It does not necessarily mean that space cannot have a specific form. In comparison to time, which is far more abstract and invisible, space is materialistic and visual. The following text will explain how space IS defined and most of all how the progress of magical-religious systems HAS transformed the perception of space. In addition I would like to stress how space is realized in literature as a three – dimensional entity. Space is defined as a path and a journey, which are also key elements of folk tales. Through an active principle that essentially defines space as well as folk tales, I have focused on the representation of specific folk tale heroes by gender.
Keywords: space; myths; Slovene folk literature; women's studies; philosophy of culture